Menstrual Cycle, Educational Commitment, and Islamic Jurisprudential Understanding: An Exploratory Mixed-Methods Study in Iraqi Higher Education - Saad Sameer Dhari; Bilal Huri Yaseen; Rehab Farooq Jad; Husam Hussien Mezban (International Tatho Academics, 2026)
The present study utilises a mixed-methods approach to analyse the psychological, physiological and educational consequences of the menstrual period among Iraqi female undergraduate students, while clarifying how Islamic rulings and linguistic interpretations of related writings notify academic activities and institutional habits. 25 Iraqi female students across two Iraqi universities completed validated psychological impact scales, symptom records, and designed questionnaires. Quantitative results showed significant relations between menstrual signs and reduced awareness, increased exhaustion, and decreased classroom involvement (p < .01). Qualitative results revealed that religious understandings concerning Muslim females' purity and attendance affect learners’ insights into academic activities during menstruation.The results shed light on gender, religion, and education in Muslim contexts and suggest a sensitive policy for institutional care procedures.